METODE SOROGAN BERBASIS TEKNOLOGI KECERDASAN BUATAN: ANALISIS APLIKASI TARTEEL - Jihan Insyira Zahrani; Ali Muthahari (Nusantara Hasana Journal, 2024)
The Sorogan Method, a classical educational paradigm prominent in Islamic institutions like pesantren, serves to impart diverse disciplines, including Al-Qur'an study. However, it grapples with time inefficiency and limited feedback. The rise of Artificial Intelligence (AI) technology presents an avenue to enhance this method. This study delves into the fusion of AI and the Sorogan Method via the Tarteel app. Employing qualitative phenomenology, it scrutinizes the outcomes of this integration. Findings from literature analysis and experiments underline that AI integration through Tarteel holds the potential to significantly amplify learning effectiveness. This research introduces an innovative paradigm, fostering a responsive, adaptive Sorogan Method, and making substantial conceptual strides in AI utilization. In turn, it lays the foundation for tech-savvy Islamic education aligned with modern dynamics.